Students as partners in action: Evaluating a university-wide initiative - Coombe, Leanne; Huang, Jasmine; Russell, Stuart; Sheppard, Karen; Khosravi, Hassan (International Journal for Students as Partners, 2018)
This case study was designed as one of many pilot projects to inform the scaling-up of Students as Partners (SaP) as a whole-of-institution strategy to enhance the student learning experience. It sought to evaluate the other pilots in order to understand the phenomena of partnerships and how students and staff perceive the experience of working in partnership. It also sought to explore the extent of benefits and challenges experienced by staff and students throughout the process and identify potential implications for future implementation.